Development of chicken egg hatching incubator machine (Natasha-CEHIM) - Mashori, Sumaiya; Azni, Nurul Natasha; Sahari, Norain; Noh, Mohd; Norjali, Rasida; Sim, Sy Yi (FAZ Publishing, 2020)
This paper presents a development of egg incubator system for chicken eggs incubation. The chicken egg hatching incubator machine are equipped with DHT22 and PIR sensors that able to automatically regulate and monitor the temperature and humidity in the incubator to create the ideal condition to incubate chicken egg. The entire system will be controlled using Arduino Uno control system as the brain of the system which control and operate the motor and sensors to detect necessary environment condition which then produce output signal for incubate operation. A DHT22 sensor that act as input detects temperature and humidity in the incubator and send it to the Arduino to display the condition of the incubator on the LCD screen display. The function of egg incubator is to be able to hatch chicks from egg while the mother hen can be free to lay more eggs hence increase the production of chicken egg, reduce the manpower, reduce hatching time and give a better efficiency during operation.